2009
DOI: 10.1002/stem.286
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Stem Cell Lines and Their Use in International Research

Abstract: Research in human pluripotent stem cells, including human embryonic stem cells (hESC) and human induced pluripotent stem cells (hiPSC), is one of the most dynamic research fields. Despite the high public attention, especially for hESC research, there is only scattered information on the number of hESC lines and the degree, dynamics, and diversification of their use on a global level. In this study we present data on the current number of publicly disclosed hESC lines, on the extent and impact of experimental w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 18 publications
3
53
1
1
Order By: Relevance
“…cells from umbilical cord or adult stem cells such as haematopoietic progenitors from bone marrow) from individuals with specific genetic backgrounds that may be associated with high risk for development of disease (patient-specific disease cell lines). Several years ago the number of established human disease cell lines was in the order of several dozens, but the number of lines available for research has grown exponentially since [summarised in 193,194]. Recently, it has been reported that patient-specific iPSC cardiomyocyte cell lines were established for common inherited cardiac arrhythmiasvarious subtypes of long QT (LQT) syndrome subtypes; the mixed phenotype of LQTS3/Brugada syndrome; subtypes 1 and 2 of catecholaminergic polymorphic ventricular tachycardia and arrhythmogenic right ventricular cardiomyopathy [23,195].…”
Section: Disease-specific Human Stem Cell Lines Get As Close As Possimentioning
confidence: 99%
“…cells from umbilical cord or adult stem cells such as haematopoietic progenitors from bone marrow) from individuals with specific genetic backgrounds that may be associated with high risk for development of disease (patient-specific disease cell lines). Several years ago the number of established human disease cell lines was in the order of several dozens, but the number of lines available for research has grown exponentially since [summarised in 193,194]. Recently, it has been reported that patient-specific iPSC cardiomyocyte cell lines were established for common inherited cardiac arrhythmiasvarious subtypes of long QT (LQT) syndrome subtypes; the mixed phenotype of LQTS3/Brugada syndrome; subtypes 1 and 2 of catecholaminergic polymorphic ventricular tachycardia and arrhythmogenic right ventricular cardiomyopathy [23,195].…”
Section: Disease-specific Human Stem Cell Lines Get As Close As Possimentioning
confidence: 99%
“…The ideal culture method is developing feeder-free culture condition (Xu et al, 2001), even chemically defined culture conditions (Ludwig et al, 2006) for human ES cells or iPS cells expansion. But so far few human ES or iPS cell lines were produced without any exposure to animal-derived compounds or in accordance with good manufacturing practices (GMP) standards (Loser et al, 2010). Therefore, culturing human ES or iPS cells in complete xeno-free conditions to reduce the risk of cross-transfer of pathogens without loss pluripotency would be a crucial prerequisite for clinical-grade applications.…”
Section: Long-term Culture and Gmp Standardsmentioning
confidence: 99%
“…According to a recent study by loser et al (25), only three heSc lines-h9, h1 and h7, derived by thomson and colleagues and provided by Wicell Research Institute, have been used in more than 50% of the scientific papers published between 1998 and 2008. Another eight cell lines (BG01, BG02, heS-2, heS-3, heS-6, hUeS7, hUeS9 and i6) account for more than 40% of the research articles that appeared during the same period.…”
Section: Human Embryonic Stem Cell Lines Inventorymentioning
confidence: 99%
“…they also have great value for the exploration of new therapeutic strategies and can provide proper testing systems for disease-oriented drug discovery. to date, 116 heSc lines with genetic disorders have been developed, representing 33 heritable human diseases (25). these lines represent only a small fraction of the large number of hereditary disorders.…”
Section: Of Mice and Men Or Why Do We Need More Disease-specific Hesmentioning
confidence: 99%